Monsters vs. aliens [videorecording (Blu-Ray)] - Stewart, Lisa; Letterman, Rob; Vernon, Conrad; Forbes, Maya; Wolodarsky, Wallace; Aibel, Jonathan, 1969-; Berger, Glenn; Witherspoon, Reese, 1976-; Rogen, Seth, 1982-; Laurie, Hugh, 1959-; Arnett, Will; Sutherland, Kiefer, 1966-; et al. (DreamWorks Pictures, 2009)
Susan Murphy gets turned into a giant monster on her wedding day when a meteorite from outer space hits her. She is taken to a secret government compound where she meets a ragtag group of monsters also rounded up over the years. As a last resort, under the guidance of General W.R. Monger, on a desperate order from The President, the motley group of Monsters are called into action to combat the aliens and save the world from imminent destruction.